Inclusive Education the way for future for Fiji schools: A comparative case study of Inclusive Education in the Czech Republic Schools in Brno and Fiji Primary Schools - Kumar, Sunil (2017)
The history of (IE) teaching within primary schools in Fiji began recently. There has been no comprehensive study of culture, policies, principles, diagnostic assessment, and education linked to teaching practices in Fiji schools. This study embarked on to examine the Inclusive teachers’ perception on inclusive education strategies, for example, culture, principles, policies, practices, diagnostic assessments, resources and the latest developments of inclusive teaching in the inclusive schools in Fiji and the Czech Republic, Brno inclusive schools. The research explored how well the teachers are equipped with knowledge and skills to undertake the teaching and learning process of inclusive education. A comparative case study research design was employed, using mixed methods with a concentration on qualitative data. The mixed methods approach is useful for capturing the strengths of both quantitative and qualitative approaches. The approach helps to overcome some of the obstacles that im